1993
DOI: 10.1093/jac/31.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily versus thrice-daily dosing of netilmicin in combination with β-lactam antibiotics as empirical therapy for febrile neutropenic patients

Abstract: In a prospective, randomized trial, netilmicin given once daily (OD) was compared in terms of efficacy and safety with the conventional 8-hourly dosing regimen (TD), both in combination with a broad spectrum beta-lactam, as initial empirical therapy for febrile neutropenic patients; the total daily dosage of netilmicin in each group was 6 mg/kg body weight. Twenty-nine of the 116 (25%) evaluable patients had microbiologically documented septicaemia, most of which were caused by Gram-positive bacteria, 41 (35%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Several trials in cancer patients with febrile neutropenia have compared aminoglycosides given once daily or several times daily with a broad-spectrum b-lactam, 23,24 all concluding that giving the aminoglycoside once daily is both efficacious and safe. However, these trials cannot be directly compared with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials in cancer patients with febrile neutropenia have compared aminoglycosides given once daily or several times daily with a broad-spectrum b-lactam, 23,24 all concluding that giving the aminoglycoside once daily is both efficacious and safe. However, these trials cannot be directly compared with our study.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] We did not observe an increased incidence of nephrotoxicity in our patient population. However, clinically significant ototoxicity occurred with greater frequency (12%) than previously reported.…”
Section: Discussionmentioning
confidence: 89%
“…Published clinical trials have suggested that SDD aminoglycosides in combination with other antimicrobials, are safe, effective, and potentially less toxic in febrile granulocytopenic cancer patients. [3][4][5][6][7][8] Based on these findings, the empiric antimicrobial regimen in the febrile neutropenic stem cell transplant (SCT) patient at MD Anderson Cancer Center was changed to include gentamicin at a dose of 5 mg/kg administered over 1 h i.v. once daily for the duration of neutropenia in marrow and peripheral blood stem cell recipients.…”
mentioning
confidence: 99%
“…More recent clinical studies have confirmed the efficacy of a single daily dose of amikacin plus ceftriaxone as a safe and effective therapy in empirical therapy of febrile granulocytopenic patients 4,5 and in children with severe gram-negative infections 6 or undergoing bone marrow transplantation. 7 It also lends itself to use alone or in combination with cephalosporins in outpatient therapy of moderate infections or in brucellosis when…”
Section: -4mentioning
confidence: 95%